Bacterial Microbiome Dynamics in Post Pull-Through Hirschsprung-Associated Enterocolitis (HAEC): An Experimental Study Employing the Endothelin Receptor B-Null Mouse Model - Cheng, Zhi; Zhao, Lifu; Dhall, Deepti; Ruegger, Paul M.; Borneman, James; Frykman, Philip K. (Frontiers in Surgery, 2018)
Purpose: Hirschsprung-associated enterocolitis (HAEC) is the most frequent potentially life-threatening complication in children with Hirschsprung disease (HSCR) even after definitive corrective surgery. Mounting evidence suggests that intestinal microbiota likely contribute to the etiology of enterocolitis, so the aim of this study was to use a mouse model of post pull-through HAEC to compare the fecal bacterial communities of animals which developed HAEC to those free of enterocolitis. Methods: Ten Ednrb−/− and 8 wild type mice underwent the microsurgical pull-through surgery, and stool was collected at the time of surgery, and then either at 2 and 4 weeks after the operation, or when the mice developed enterocolitis. The mid-colon of all animals was collected, prepared and histologically graded for enterocolitis. Fecal DNA was isolated and bacterial 16S rRNA genes analyzed using Illumina sequencing. Results: Six Ednrb−/− mice developed HAEC with a mean enterocolitis score of 5.7, while the remaining 4 mutant and 8 WT mice remained free of enterocolitis by 4 weeks. The HAEC group had lower alpha diversity by Chao1 analysis compared with WT group, while the Ednrb−/− mice demonstrated distinct bacterial communities from WT mice on beta diversity analysis. The most striking finding was increased proportion of Akkermansia and reduced Bacteroidetes compared with the NO HAEC and WT groups, suggesting Akkermansia may contribute to development of enterocolitis while Bacteroidetes may be protective. Less abundant genera that were reduced in HAEC were Dysgonomas and Clostridium XIVa which may play a protective role. Conclusions: This is the first study to identify Akkermansia as potentially playing a role in HAEC, either as a pathobiont taxa contributing to pathogenesis of enterocolitis, or possibly a protective commensal taxa expanded in response to inflammation. These findings characterized the dynamic shifts in the gut microbial communities through the onset of post pull-through HAEC, and suggests that there may be identifiable bacterial community differences in HSCR patients that are high risk for developing HAEC.